HPLC evaluation on 3-n-butylphthalide distribution - Qi Wang & , Shuoyang Li, Peifeng Liu, Ming Shen, Tao Gong, Yourong Duan, Zhang Zhi-Rong (Journal of Applied Pharmaceutical Science)
A rapid, sensitive and speciï¬c reversed-phase high-performance liquid chromatographic method was developed for the determination of 3-n-butylphthalide, a drug currently being developed for treatment of stroke, in mice tissue. Ultraviolet detection were monitored at 228 nm for quantiï¬cation of 3-n-butylphthalide. Ibuprofen was used as internal standard. The peak area ratio vs concentration in tissue was linear over the range of 25.625–1025.000 ng/mL and the limit of quantiï¬cation was 25.625 ng/mL. The method was successfully applied to pharmacokinetic investigation in mice. The mean distribution half-life was 5.471 ± 4.736 min and elimination half-life was 58.459 ± 34.370 min. Finally, a preclinical bio-distribution research of 3-n-butylphthalide in mice following intravenous administration had been studied. Brain targeting of 3-n-butylphthalide was strong and metabolism in the liver and blood was rapid.
Keywords: HPLC,3-n-Butylphthalide,Pharmacokinetic investigation,Distribution.